Effects of leaf and plant age on specific leaf area in deciduous tree species Quercus cerris L. var. Cerris - Karavin, Neslihan (Bangladesh Journal of Botany, 2014)
In Quercus cerris L. var. cerris, four diameters at breast height (BDH) groups were selected as a surrogate for approximate plant age groups to study the effects of plant and leaf age on leaf dry mass, leaf area and specific leaf area. The forms of fluctuations in specific leaf area (SLA) of all DBH groups were similar during the growth period. The minimum SLA was calculated at the leaves mature phase. Leaf area did not differ significantly according to leaf age. Significant differences caused by leaf age were determined in mean leaf dry mass and SLA. No significant differences in mean SLA caused by plant age were found. Leaf area and leaf dry mass significantly varied among DBH groups. Leaf area was positively correlated with leaf dry mass, and SLA was negatively correlated with leaf dry mass, while there was no significant relationship with leaf area. DOI: http://dx.doi.org/10.3329/bjb.v42i2.18034 Bangladesh J. Bot. 42(2): 301-306, 2013 (December)